2014
DOI: 10.1186/1752-4458-8-13
|View full text |Cite
|
Sign up to set email alerts
|

Depression among AIDS-orphaned children higher than among other orphaned children in southern India

Abstract: BackgroundSystematic data on mental health issues among orphaned children are not readily available in India. This study explored depression and its associated risk factors among orphaned children in Hyderabad city in south India.Methods400 orphaned children drawn equally from AIDS and non-AIDS orphan groups aged 12–16 years residing in orphanages in and around Hyderabad city in southern India were recruited to assess depression and associated risk factors using the Center for Epidemiologic Studies-Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…Consistent with previous research, our findings confirm that ALHIV had higher orphan rates than the general adolescent population in Namibia (62.6% vs. 15.7%), with 17.2% (vs. 2.7%) being double orphans (Namibia Statistics Agency, ). However, the finding that orphans did not have more mental health problems was unexpected, as previous research has shown that children orphaned due to AIDS, a high likelihood in the current study, are more vulnerable compared with other orphans (Cluver, Orkin, Gardner, & Boyes, ; Kumar, Dandona, Kumar, Ramgopal, & Dandona, ). However, associated variables, such as poverty or whether the orphan lives in a rural area, may impact this relationship.…”
Section: Discussioncontrasting
confidence: 47%
“…Consistent with previous research, our findings confirm that ALHIV had higher orphan rates than the general adolescent population in Namibia (62.6% vs. 15.7%), with 17.2% (vs. 2.7%) being double orphans (Namibia Statistics Agency, ). However, the finding that orphans did not have more mental health problems was unexpected, as previous research has shown that children orphaned due to AIDS, a high likelihood in the current study, are more vulnerable compared with other orphans (Cluver, Orkin, Gardner, & Boyes, ; Kumar, Dandona, Kumar, Ramgopal, & Dandona, ). However, associated variables, such as poverty or whether the orphan lives in a rural area, may impact this relationship.…”
Section: Discussioncontrasting
confidence: 47%
“…In the multiple linear regression models, variables were included when they were found to be associated with depressive symptoms in previous studies. These variables were age, HIV status, orphan status, sibling care practices, food security, general health status, ACEs, family dysfunction, and school attachment [ 23 , 28 , 34 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Uganda, one of the countries hardest hit by the epidemic in SSA, 1.2 million children are orphaned as a direct result of HIV/AIDS (UNICEF, 2016). For orphaned children, these negative effects include economic hardships, poor schooling and education outcomes, poor physical and mental health functioning because of psychological distress, stigma and discrimination, and the loss of social support from both the household and the community (Atwine, Cantor-Grace, & Bajunirwe, 2005;Chi & Li, 2013;Cluver, Orkin, Gardner, & Boyes, 2012;Foster & Williamson, 2000;Klein, Dougherty, & Olino, 2005;Kumar, Dandona, Kumar, Ramgopal, & Dandona, 2014;Lata & Verma, 2013;Nyambedha & Aagaard-Hansen, 2010). For orphaned children, these negative effects include economic hardships, poor schooling and education outcomes, poor physical and mental health functioning because of psychological distress, stigma and discrimination, and the loss of social support from both the household and the community (Atwine, Cantor-Grace, & Bajunirwe, 2005;Chi & Li, 2013;Cluver, Orkin, Gardner, & Boyes, 2012;Foster & Williamson, 2000;Klein, Dougherty, & Olino, 2005;Kumar, Dandona, Kumar, Ramgopal, & Dandona, 2014;Lata & Verma, 2013;Nyambedha & Aagaard-Hansen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…HIV/AIDS negatively affects not only the affected individual but also their household livelihoods and community safety nets. For orphaned children, these negative effects include economic hardships, poor schooling and education outcomes, poor physical and mental health functioning because of psychological distress, stigma and discrimination, and the loss of social support from both the household and the community (Atwine, Cantor-Grace, & Bajunirwe, 2005;Chi & Li, 2013;Cluver, Orkin, Gardner, & Boyes, 2012;Foster & Williamson, 2000;Klein, Dougherty, & Olino, 2005;Kumar, Dandona, Kumar, Ramgopal, & Dandona, 2014;Lata & Verma, 2013;Nyambedha & Aagaard-Hansen, 2010).…”
Section: Introductionmentioning
confidence: 99%